Strategi Komunikasi Website Berita infopasraman.com Dalam Upaya Mempromosikan Sekolah Berbasis Pendidikan Keagamaan Hindu - I Made Bagus Andi Purnomo; Roni Han Wasisto (Jayapangus Press, 2022)
Since the first time the existence of regulations regarding Hindu religious education. The public has not found a news website that focuses on reporting about pasraman. Pasraman meant both formal and non-formal. The presence of the infopasraman.com news website provides very encouraging news to academics and practitioners of religious education. The purpose of this study was to determine the communication strategy of the infopasraman.com news website in an effort to promote Hindu religious education-based schools. Furthermore, to understand the obstacles and obstacles to the implementation of the infopasraman.com news website communication strategy in an effort to promote Hindu religious education-based schools and thirdly to find out the impact of the infopasraman.com news website communication strategy on the development of formal pasraman in Indonesia. Qualitative research methods are more based on the philosophy of phenomenology that prioritizes appreciation (verstehen). The research uses qualitative data sources and the research instrument is the researcher himself. The research results show that the infopasraman.com News Website Communication strategy in an effort to promote Hindu religious education/formal pasraman schools in Indonesia is in the form of the following scope: a) Doing objective reporting; b) Take the initiative to communicate and expand the network; c) Focus on pasraman news; d) Flexibility with contributors to pasraman news in various regions; honesty in management and management; e) Maintain security when carrying out journalistic duties; and f) Innovate in implementing digital media convergence. The obstacles and obstacles in implementing the communication strategy of the infopasraman.com news website are divided into two, namely internal and external barriers. The impact of the infopasraman.com news website is the impact of socialization, connectivity and supervision.